3D Finite Element Analysis of Implant-supported Fixed Partial Denture Frameworks Fabricated from Fiber-reinforced Composite and Polyetheretherketone. - Azher Mazin Agha; Ahmed Asim Saeed Al-Ali; Ayad Amjad Abdulrazzak (University of Mosul, College of Dentistry, 2024)
Aims: This study aimed to test different design parameters for ISFPD frameworks fabricated from fiber-reinforced composite and polyetheretherketone. Material and Methods: 12 different framework digital designs made using the AutoCAD program were sent to Autodesk Inventor 2023 for finite element analysis (FEA), these designs included 6 different connector designs according to cross-sectional shape and height-to-width ratio as follows: (ellipse3:2, ellipse 4:3, round, ellipse3:4, ellipse2:3 and triangular9:8) with 2 different connector cross-sectional areas (12mm2 and 16mm2) and were presented to the FEA program as two different materials (PEEK and FRC) to study stress distribution and displacement under 800N load. Stress and displacement values were used to determine the suitable framework material, connector cross-sectional area, and design. Results: FEA had resulted in FRC frameworks exhibiting higher resistance to bending than PEEK frameworks. 16mm2 connector cross-sectional area resulted in higher resistance to loading than 12mm2 connectors. Ellipse connectors with 3:2 height-to-width designs also resulted in the highest resistance to bending compared to other designs. Triangular designs resulted in the highest areas of stress concentration among other designs. Conclusions: Framework design should be considered to allow safe usage of PEEK and FRC as framework materials, FRC framework is more resistant to bending, and increasing the height of the connector increases the resistance to bending thus making ellipse designs with higher height-to-width ratio better in resistance to bending, triangular cross-section designs are not recommended.